KARAKTERISTIK DEMOGRAFI, SOSIAL DAN EKONOMI SUMBER DAYA PEMUDA INDONESIA - Kasto Kasto (Populasi, 1995)
The productivity of youth must be increased in the development process of Indonesia. According to the 1990 population census, there are 50.7 million youths (people at the age between 15-29years). Out of that number, only 52.1 percent who have directly participated in the development process, because their main activities are working. Of the rest, 20.6 percent took care of houses; 17.1percent studied; 3.6 percent were looking for a job, and 6.6 percent were included in the non productive group. Out of 52.1 percent or 26.4 million youth who worked, 33.4 percent worked below the normal working hours (less than 35 hours per week). Based on the field of work, 52.8 percent worked in the agricultural sector. According to the type of job, 91.2 percent worked as rough or unskilled workers, and based on the work status, 65.1percent worked in the informal sectors. These numbers reflect on the low quality of Indonesia's youth labor force, and this must be immediately removed, mainly through education, remembering that 61.6 percent of youths have no more than primary education.